Tree Diversity and Endemism Pattern in Makutta Wildlife Range, Western Ghats, India - Neikha, Vimhaseno; Nagaraja, B. C. (Indian Forester, 2019)
Species diversity and endemism pattern of the trees along the elevational gradients were studied in the Makutta Wildlife Range of the Western Ghats in Kodagu district. A total of 604 individuals belonging to 68 species, 55 genera and 30 families were identified between 100 to 800 m. Among these, 26 tree species were endemic to the Western Ghats region belonging to 14 families. The species composition varied from 17 species at 800 m to 27 at 400 m. The Shannon-Wiener diversity index scored a maximum value of 3.02 at 400 m indicating higher species diversity in this elevation. The overall species richness and endemism showed a hum shaped pattern along the elevational gradients with peaks at two different elevations each. The study indicates the presence of a diverse flora in the Makutta Wildlife Range, hence continued efforts must be made for conservation of these areas.